Innovation Leadership affecting Innovative Behavior of Personnel in Local Administrative Organizations in the Southern Border Provinces - Srisuk, Tanyakorn; Phayoonpun, Thammayantee (Princess of Naradhiwas University Journal of Humanities and Social Sciences, 2023)
DOI: 10.14456/pnuhuso.2023.6 This quantitative research aims to study innovation leadership: 1) skills affecting innovative behavior 2) personality affecting innovative behavior 3) social characteristics affecting innovative behavior and 4) roles affecting innovative behavior. The samples were 400 staff members of local administrative organizations in the southern border provinces, selected by simple random sampling. The research instruments were questionnaires. Data were analyzed by descriptive approach. The statistics used for analyzing data were frequent, percentage, mean, standard deviation, and multiple regression analysis. The results revealed that the components of innovation leadership affecting innovative behavior were the social characteristics and roles aspects. However, the components of innovation leadership that did not lead to innovative behavior were the skills and personality aspects.